THE EVIDENCE AND IMPLICATIONS OF POLAR ICE DURING THE MESOZOIC - Price G.D. (My University, 1999)
Long periodic geodynamic processes with durations between 150 and 600 Million years appear to be in phase with similar galactic cycles, caused by the path of the solar system through the spiral arms of the Milky Way. This path is assumed by some authors to cause climate change due to cosmic ray fluctuations, affecting the cloud formation and the related albedo of the Earth, which periodically lead to glaciations every 150 Ma. With the glaciations, the sea level fluctuates accordingly. Subsequently, the varying sizes of shallow seas are causing periodic changes of the Moon’stidal dissipation, which affects presumably other geodynamic processes on the Earth. The Moonmay therefore synchronize directly or indirectly long periodic Phanerozoic cycles (sea level, orogeny, magmatism, sedimentation, etc.) with the Milky Way. As sea level fluctuations, orogeny, sedimentation and magmatism can be described as members of a geodynamic feedback system; no apparent reasons appear to be required to assign a cause of the cyclicity to agents outside of thegalactic-climatically synchronized Earth-Moon system. However, recent observations of youngvolcanism on the near Earth terrestrial planets may require a new understanding. Magmatic/volcanic episodes on Venus, Mars and Mercury as well as on the Earth’s Moon are apparently contemporaneous thermal events accompanying increased magmatic/volcanic activities on theEarth,following a 300 myr cycle. Therefore, a collateral galactic thermal source within the Milky Wayappears to be needed that only affects the interior of the planets without any recognizable directeffect on life and geology on the Earth. The search for such a source may lead to astrophysicalquestions, related to a spiral arm affected distribution of dark energy, dark matter or even specificneutrino sources. However, all possible astrophysical answers are outside of the author’s competence.
Keywords: Mesozoic; Mesozoic; Мезозой